Investigasi aquifer dengan metode inversi smoothness-constraint least squares data geolistrik tahanan jenis konfigurasi schlumberger di Bukit Apit Puhun Kecamatan Guguk Panjang Kota Bukittinggi (Aquifer investigation using smoothness-constraint least squares inversion method of geoelectric resistivity schlumberger configuration in Bukit Apit Puhun, Guguk Panjang District, Bukittinggi City) - Imran Razat; - Akmam; - Mahrizal (Department of Physics – Universitas Negeri Padang UNP, 2015)
Bukit Apit Puhun was one of the area that need to know information about the depth of the aquifer layer. Bukit Apit Puhun located at Sianok canyon a valley surrounded by hills composed by a layer of igneous rocks. Layers of rock in the Sianok canyon assumed can store groundwater reserves. This research used the resistivity geoelectrical methode with Schlumberger configuration. The data were processed and interpreted by the Smoothness Constraint Least-Squares inversion. The data were taken five track using ARES (Automatic Resistivitymeter). The result of this research showed that the material contained in the Bukit Apit Puhun was Clay, Sandstone, Limestone and Andesite. The material contained in the study area shows that the area was a water catchment area with no finding of aquifer layers in every track. Results of this study were not strengthened by the discovery of a well to track the location of measurement